Family Empowerment to Fullfillment Nutrition in Stunted Children - Hastuti, Apriyani Puji; Suprawoto, Dina Nurpita; Roesardhyati, Ratna; Kurniawan, Ardhiles Wahyu; Soares, Domingos; Fani, Rif'atul (Babali Publisher, 2024)
Background: This research aims to analyze family empowerment in efforts to fulfill nutritional requirements for children aged 6-24 months who are stunted. Method: The method used was a quasi-experiment with a pre-post test control group design approach to 72 mothers in each group. Result: The results of the research show that there is a difference in mothers' ability to fulfill nutrition in terms of complementary feeding and responsive feeding after being given family empowerment interventions in families with stunted children aged 6-24 months, namely food preparation and processing (p=0.000), complementary feeding (p= 0.000), responsive feeding (p=0.000). Conclusion: So it is hoped that family empowerment is an effort to strengthen its role in handling and accelerating the reduction in stunting incidents.